Composite collector containing pyridine ionic liquid and its application in preparation of high-purity quartz by flotation
Patent Information
- Application Number
- CN202611336894.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]现有研究也尝试将吡啶类阳离子药剂用于石英-长石浮选分离,公开号为CN116689159 A的中国发明专利申请公开了一种中性条件下的长石石英分离方法,虽然采用了N-正丁基氯化吡啶和月桂基磺酸钠作为复合捕收剂对石英进行浮选,但该申请所采用的短链吡啶离子液体复配体系自身浮选性能有限,需要进一步搭配十二胺共同使用,才能够获得满足要求的石英精矿;不仅药剂复配体系复杂,增加了浮选工艺流程控制难度,同时提升药剂使用成本,仍有进一步改进提升的空间
[0024](1)本发明采用长链氯化-N-烷基吡啶与磷酸酯改性油酸进行复配,二者产生显著协同浮选效应。长链氯化-N-烷基吡啶借助吡啶环的强极性与共轭效应,可在 pH 为 3 的酸性矿浆条件下优先选择性吸附于长石、云母等铝硅酸盐矿物表面,几乎不在石英表面发生吸附;且长烷基链提供强疏水性;磷酸酯改性油酸同时带有羧基、羟基以及磷酸酯螯合位点,一方面可与铝硅酸盐矿物表面铝位点发生螯合吸附,另一方面能够与长链吡啶阳离子形成离子缔合复合物,进一步加快药剂在脉石矿物表面的吸附动力学,强化对铝硅酸盐脉石的捕收选择性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of quartz flotation technology, specifically to a composite collector containing pyridine-based ionic liquids and its application in the flotation preparation of high-purity quartz. Background Technology
[0002] High-purity quartz (SiO2 mass fraction > 99.99%) is a key raw material for the photovoltaic industry, semiconductor devices, and optical glass manufacturing. In the industrial preparation of high-purity quartz, aluminosilicate gangue minerals such as feldspar and mica, as well as iron impurities, are the main harmful components restricting the purity of quartz products. Current industrial production often uses hydrofluoric acid combined with amine or etheramine collectors for flotation to remove these impurities. However, the hydrofluoric acid process is highly corrosive, poses a high environmental risk, and puts significant pressure on waste treatment, leading to its gradual phasing out. Traditional amine collectors, such as dodecylamine and etheramine, have insufficient flotation selectivity, requiring 3-5 multiple cleaning operations to meet the impurity requirements of high-purity quartz, resulting in a complex flotation process and a long production cycle. Furthermore, these reagents are prone to quartz particle entrainment under low pH flotation conditions, leading to low single-flotation recovery rates of quartz concentrate, generally below 85%. Additionally, the high cost of etheramine collectors contributes to the high cost of high-purity quartz production. Therefore, developing a collector with good flotation selectivity, high quartz recovery rate, and the ability to shorten the flotation operation cycle and reduce reagent consumption in the mineral processing section is an urgent need in the field of high-purity quartz flotation purification.
[0003] Existing research has also attempted to use pyridine cationic reagents for quartz-feldspar flotation separation. Chinese invention patent application CN116689159 A discloses a method for separating feldspar and quartz under neutral conditions. Although it uses N-n-butylpyridine chloride and sodium lauryl sulfonate as a composite collector for quartz flotation, the short-chain pyridine ionic liquid composite system used in this application has limited flotation performance on its own. It needs to be further combined with dodecylamine to obtain quartz concentrate that meets the requirements. Not only is the reagent composite system complex, which increases the difficulty of controlling the flotation process, but it also increases the cost of reagent use. There is still room for further improvement. Summary of the Invention
[0004] The purpose of this invention is to address the aforementioned problems by providing a novel compound collector for the purification of high-purity quartz using pyridine-based ionic liquids. This collector is composed of a mixture of pyridine-based ionic liquids and phosphate-modified oleic acid, which can efficiently remove aluminosilicate gangue minerals such as feldspar and mica with a shorter stirring time, thereby improving the recovery rate of quartz concentrate, reducing the number of flotation and beneficiation operations, lowering the total reagent consumption in the beneficiation stage, and facilitating the overall cost control of high-purity quartz purification.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] A composite collector containing pyridine ionic liquid is mainly composed of pyridine ionic liquid and phosphate-modified oleic acid in a mass ratio of 2 to 4:1. The pyridine ionic liquid is N-chloroalkylpyridine, wherein the alkyl chain length is C12 to C18. The phosphate-modified oleic acid is prepared by epoxidation and ring-opening followed by phosphorylation.
[0007] In this invention, preferably, the phosphate-modified oleic acid is prepared by the following method:
[0008] S1 Epoxidation: Oleic acid and formic acid are mixed, heated to 55-65℃, and 30% hydrogen peroxide is added dropwise to carry out the epoxidation reaction. After the reaction is completed, the organic phase is separated and washed with water until neutral to obtain epoxy oleic acid; wherein, the mass ratio of oleic acid to formic acid is 100:8-12, and the mass ratio of oleic acid to hydrogen peroxide is 100:30-35.
[0009] S2 acid-catalyzed ring-opening hydroxylation: Water and concentrated sulfuric acid catalyst are added to epoxy oleic acid, and the mixture is stirred vigorously at 70–80°C to carry out the ring-opening reaction to obtain hydroxy oleic acid; the mass ratio of epoxy oleic acid to water is 100:20–25, and the mass of concentrated sulfuric acid is 0.8%–1.2% of the mass of epoxy oleic acid;
[0010] S3 Phosphoric acid esterification: Phosphorus pentoxide is added in batches to hydroxyoleic acid at 65-75℃ to carry out the esterification reaction. The molar ratio of hydroxyoleic acid to phosphorus pentoxide is 2.5-3:1. After esterification, water is added for aging.
[0011] S4 Neutralization: The system is cooled to below 40°C and neutralized with triethanolamine to a pH of 6.4–6.6 to obtain phosphate-modified oleic acid.
[0012] In this invention, preferably, during the maturation process in step S3, the amount of water added is 4% to 6% of the total mass of the system, the maturation temperature is 65 to 75°C, and the maturation time is 1 to 2 hours.
[0013] In this invention, preferably, the mass ratio of pyridine ionic liquid to phosphate-modified oleic acid in the composite collector is 3.3:1.
[0014] This invention also provides the application of composite collectors in the flotation preparation of high-purity quartz.
[0015] Specifically, the flotation preparation of high-purity quartz includes the following steps:
[0016] (1) The raw quartz ore is ground and pulped to obtain a slurry;
[0017] (2) Add inorganic acid to adjust the pH of the slurry to 3.0-3.5;
[0018] (3) Add the composite collector and perform at least one roughing flotation and one fine flotation.
[0019] In the above steps, preferably, the total amount of the composite collector is 800-900 g / t based on the mass of the raw ore.
[0020] In the above steps, preferably, the total time for adjusting the pulp and scraping bubbles in the roughing and fine flotation in step (3) does not exceed 5 minutes.
[0021] In the above steps, preferably, during the pulping process in step (1), the mass concentration of the pulp is controlled to be 15-20%.
[0022] In the above steps, preferably, in step (1), the particle size distribution of the ore powder obtained by grinding is 0.1 mm to 0.3 mm.
[0023] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0024] (1) In this invention, long-chain chlorinated N-alkylpyridine and phosphate-modified oleic acid are combined to produce a significant synergistic flotation effect. The long-chain chlorinated N-alkylpyridine, with the strong polarity and conjugation effect of the pyridine ring, can preferentially and selectively adsorb onto the surface of aluminosilicate minerals such as feldspar and mica under acidic slurry conditions with a pH of 3, and hardly adsorbs onto the quartz surface; and the long alkyl chain provides strong hydrophobicity; the phosphate-modified oleic acid has carboxyl, hydroxyl and phosphate chelation sites, which can chelate and adsorb onto the aluminum sites on the surface of aluminosilicate minerals, and form ion-associated complexes with long-chain pyridine cations, further accelerating the adsorption kinetics of the reagent on the surface of gangue minerals and enhancing the collection selectivity of aluminosilicate gangue.
[0025] (2) The reagent of this invention has high reactivity and excellent dispersion performance in slurry, which can increase the contact angle of gangue minerals. The reagent adsorption can be completed with only 1 to 2 minutes of stirring and slurry preparation, without the need for long slurry preparation. The flotation speed is significantly improved compared with traditional amine collectors, realizing short-process and high-efficiency purification. After one roughing and at least one cleaning flotation operation, the aluminosilicate gangue minerals that have been liberated can be almost completely removed, and the Al2O3 content in quartz ore can be reduced from 0.63% to below 0.0017%. The quartz concentrate obtained by flotation treatment with this collector, combined with traditional calcination, acid leaching and other purification processes, can achieve a high purity of 99.995% quartz sand.
[0026] (3) The reagent of the present invention has excellent selectivity and rarely carries quartz minerals into the foam product. The quartz concentrate recovery rate can reach more than 95%, which effectively alleviates the industry problem of "removing impurities inevitably damages the product" in the existing high-purity quartz flotation.
[0027] (4) Compared with the mainstream and expensive ether amine collectors on the market, the pyridine ionic liquid raw material used in this invention is readily available and is compounded with fatty acid modified components; according to calculations, the reagent consumption cost per unit of the flotation application section is lower than that of traditional ether amine reagents. At the same time, this flotation system is a fluorine-free flotation system, avoiding the defects of high corrosion and high pollution of hydrofluoric acid process, and has excellent prospects for industrial application. Detailed Implementation
[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0029] Unless otherwise specified, the operating and testing methods involved in the following embodiments are conventional operating and testing methods already existing in the prior art. Unless otherwise specified, the equipment and raw materials involved in the following embodiments are conventional equipment and raw materials already existing in the prior art and can be obtained through legitimate commercial channels. In the embodiments of the present invention, the phosphate-modified oleic acid used was prepared in-house in a small-scale laboratory.
[0030] Preparation Examples of Raw Material Phosphate-Modified Oleic Acid
[0031] Example 1
[0032] A method for preparing phosphate-modified oleic acid includes the following steps:
[0033] S1. Epoxidation: Oleic acid and formic acid with a mass fraction of 88% are added to the reactor at a mass ratio of 100:10. The mixture is stirred and heated to 60°C. Hydrogen peroxide with a mass fraction of 30% is added dropwise at a uniform rate at a mass ratio of 100:32 for 1.5 hours. After the addition is complete, the mixture is kept at this temperature for 4 hours. After the reaction is completed, the mixture is allowed to stand and separate into layers. The upper organic phase is taken and washed with deionized water until the washing liquid is pH neutral. The mixture is then dehydrated under reduced pressure to remove residual water and small molecule impurities, yielding refined epoxy oleic acid.
[0034] S2, Acid-catalyzed ring-opening hydroxylation: Deionized water and 98wt% concentrated sulfuric acid catalyst were added to epoxy oleic acid; the mass ratio of epoxy oleic acid to deionized water was 100:22, and the amount of concentrated sulfuric acid added was 1.0% of the mass of epoxy oleic acid; under strong stirring at 550 r / min, the ring-opening reaction was carried out at 75℃ for 3 h to obtain hydroxy oleic acid.
[0035] S3, Phosphoric acid esterification: The system temperature is controlled at 70℃±1. According to the molar ratio of hydroxyoleic acid to phosphorus pentoxide of 2.8:1, phosphorus pentoxide powder is added in 5 batches with an interval of 15 minutes between each batch. After the addition is completed, the esterification is maintained at the temperature for 4 hours. Then, 5% of the total mass of deionized water is added and the mixture is kept at 70℃ for 1.5 hours for curing.
[0036] S4. Neutralization and conditioning: Cool the system to about 38°C, slowly add triethanolamine to neutralize, stir evenly, and control the pH to stabilize at 6.5 to obtain phosphate-modified oleic acid.
[0037] Product analysis: Acid value 192 mgKOH / g; monophosphate ester mass fraction 61.2%; diephosphate ester mass fraction 34.5%; free phosphoric acid mass fraction 0.95%; iodine value 49 g / 100g. The product is a light yellow, transparent, viscous liquid; a 1% aqueous solution has a pH of 6.5.
[0038] Infrared spectrum (KBr pellet): 1735 cm⁻¹ -1 A stretching vibration peak of the carboxyl group C=O appears at 1240 cm⁻¹. -1 A P=O stretching vibration peak appears at 1030 cm⁻¹. -1 The appearance of the POC stretching vibration peak indicates that a phosphate ester group has been successfully introduced into the oleic acid molecule.
[0039] Example 2
[0040] A method for preparing phosphate-modified oleic acid includes the following steps:
[0041] S1. Epoxidation: Oleic acid and formic acid with a mass fraction of 88% are added to the reactor at a mass ratio of 100:8. The mixture is stirred and heated to 55°C. Hydrogen peroxide with a mass fraction of 30% is added dropwise at a uniform rate at a mass ratio of 100:30 for 1.5 hours. After the addition is complete, the mixture is kept at this temperature for 4 hours. After the reaction is completed, the mixture is allowed to stand and separate into layers. The upper organic phase is taken and washed with deionized water until the washing liquid is pH neutral. The mixture is then dehydrated under reduced pressure to remove residual water and small molecule impurities, yielding refined epoxy oleic acid.
[0042] S2, Acid-catalyzed ring-opening hydroxylation: Deionized water and 98wt% concentrated sulfuric acid catalyst were added to epoxy oleic acid; the mass ratio of epoxy oleic acid to deionized water was 100:20, and the amount of concentrated sulfuric acid added was 0.8% of the mass of epoxy oleic acid; under strong stirring at 500 r / min, the ring-opening reaction was carried out at 70℃ for 3 h to obtain hydroxy oleic acid.
[0043] S3, Phosphoric acid esterification: The system is kept at a constant temperature of 65℃. Phosphorus pentoxide powder is added in 5 batches with an interval of 15 minutes between each batch, according to the molar ratio of hydroxyoleic acid to phosphorus pentoxide of 2.5:1. After the addition is completed, the system is kept at a constant temperature for 4 hours for esterification. Then, 4% of the total mass of deionized water is added and the system is kept at 65℃ for 2 hours for curing.
[0044] S4. Neutralization and conditioning: Cool the system to about 38°C, slowly add triethanolamine for neutralization, stir evenly, and control the pH to stabilize at 6.4 to obtain phosphate-modified oleic acid.
[0045] Product analysis: Acid value 186 mgKOH / g; monophosphate ester mass fraction 58.3%; diephosphate ester mass fraction 36.2%; free phosphoric acid mass fraction 1.12%; iodine value 53 g / 100g. The product is a light yellow, transparent, viscous liquid; a 1% aqueous solution has a pH of 6.4.
[0046] Infrared spectrum (KBr pellet): 1733 cm⁻¹ -1 A stretching vibration peak of the carboxyl group C=O appears at 1238 cm⁻¹. -1 A P=O stretching vibration peak appears at 1028 cm⁻¹. -1 The appearance of the POC stretching vibration peak indicates that a phosphate ester group has been successfully introduced into the oleic acid molecule.
[0047] Example 3
[0048] A method for preparing phosphate-modified oleic acid includes the following steps:
[0049] S1. Epoxidation: Oleic acid and 88% formic acid (mass fraction) are added to the reactor at a mass ratio of 100:12. The mixture is stirred and heated to 65°C. Hydrogen peroxide (mass fraction) of 30% (mass fraction) is added dropwise at a uniform rate at a mass ratio of 100:35 (oleic acid:hydrogen peroxide), with a dropping time of 1.5 h. After the addition is complete, the mixture is kept at this temperature for 4 h. After the reaction is completed, the mixture is allowed to stand and separate into layers. The upper organic phase is taken and washed with deionized water until the washing liquid is pH neutral. The mixture is then dehydrated under reduced pressure to remove residual water and small molecule impurities, yielding refined epoxy oleic acid.
[0050] S2, Acid-catalyzed ring-opening hydroxylation: Deionized water and 98wt% concentrated sulfuric acid catalyst were added to epoxy oleic acid; the mass ratio of epoxy oleic acid to deionized water was 100:25, and the amount of concentrated sulfuric acid added was 1.2% of the mass of epoxy oleic acid; under strong stirring at 600 r / min, the ring-opening reaction was carried out at 80℃ for 3 h to obtain hydroxy oleic acid.
[0051] S3, Phosphoric acid esterification: The system is kept at a constant temperature of 75℃±1. Phosphorus pentoxide powder is added in 5 batches with an interval of 15 minutes between each batch, according to the molar ratio of hydroxyoleic acid to phosphorus pentoxide of 3:1. After the addition is completed, the system is kept at a constant temperature for 4 hours for esterification. Then, 6% of the total mass of deionized water is added and the system is kept at 75℃ for 1 hour for curing.
[0052] S4. Neutralization and conditioning: Cool the system to about 38°C, slowly add triethanolamine for neutralization, stir evenly, and control the pH to stabilize at 6.6 to obtain phosphate-modified oleic acid.
[0053] Product analysis: Acid value 201 mg KOH / g; monophosphate ester mass fraction 59.5%; diephosphate ester mass fraction 35.3%; free phosphoric acid mass fraction 1.04%; iodine value 46 g / 100g. The product is a brownish-yellow transparent viscous liquid, and the pH of a 1% aqueous solution is 6.6.
[0054] Infrared spectrum (KBr pellet): 1736 cm⁻¹ -1 A stretching vibration peak of the carboxyl group C=O appears at 1242 cm⁻¹. -1 A P=O stretching vibration peak appears at 1032 cm⁻¹. -1 The appearance of the POC stretching vibration peak indicates that a phosphate ester group has been successfully introduced into the oleic acid molecule.
[0055] Flotation Examples of High-Purity Quartz
[0056] The following flotation tests are all small-scale laboratory tests, using a laboratory single-cell flotation machine to conduct reverse flotation tests. The froth product is gangue tailings, and the product in the flotation cell is quartz concentrate. The ore detection data are the results of the main oxide detection, and trace components such as loss on ignition are not included. The sum of the components is slightly greater than 100%, which is within the normal error range of mineral detection.
[0057] Example 4
[0058] Raw materials: mineral processing feed from a quartz sand plant in Fengyang, Anhui Province (Al2O3 content 0.63%, SiO2 content 99.3%) after crushing and screening.
[0059] Reagent: Chlorinated N-hexadecylpyridine and phosphate-modified oleic acid are mixed at a mass ratio of 3.3:1.
[0060] process:
[0061] (1) Grind and screen the raw quartz ore to obtain 100% mineral powder with a particle size of 0.3mm to 0.1mm, and add water to adjust it to obtain a slurry with a mass concentration of 18%;
[0062] (2) Add sulfuric acid to adjust the pH of the slurry to 3.2;
[0063] (3) Roughing operation: Add compound collector to the slurry, the amount of roughing agent is 400g / t (based on the weight of the raw ore, that is, 0.400g collector is added per kilogram of raw ore), stir and adjust the slurry for 2 minutes, aerate and scrape the foam for 3 minutes, the foam is the roughing tailings; the roughing concentrate is obtained in the flotation cell;
[0064] Fine-grained process: The rougher concentrate is transferred to the flotation machine. The pH of the pulp is not adjusted. The compound collector is added again, with a fine-grained reagent dosage of 300g / t (based on the weight of the raw ore, i.e., 0.300g collector per kilogram of raw ore). The pulp is stirred and conditioned for 1 minute, then aerated and skimmed for 3 minutes. The foam is the fine-grained tailings. The compound collector is added again, with a fine-grained reagent dosage of 200g / t (based on the weight of the raw ore, i.e., 0.200g collector per kilogram of raw ore). The pulp is stirred and conditioned for 1 minute, then aerated and skimmed for 2 minutes. The foam is the fine-grained tailings. The product in the flotation cell is the quartz concentrate.
[0065] Results: The product obtained in the tank (quartz concentrate) had the following properties: SiO2 content 99.996%, Al2O3 content 0.0011%, and quartz concentrate recovery rate 95.3%.
[0066] Example 5
[0067] Raw materials: mineral processing feed from a quartz sand plant in Fengyang, Anhui Province (Al2O3 content 0.63%, SiO2 content 99.3%) after crushing and screening.
[0068] Reagent: Chlorinated N-hexadecylpyridine and phosphate-modified oleic acid are mixed in a mass ratio of 2:1.
[0069] process:
[0070] (1) Grind and screen the raw quartz ore to obtain 100% mineral powder with a particle size of 0.3mm to 0.1mm, and add water to prepare a slurry with a mass concentration of 20%;
[0071] (2) Add sulfuric acid to adjust the pH of the slurry to 3.2;
[0072] (3) Roughing operation: Add compound collector to the slurry, the amount of roughing agent is 550g / t (based on the weight of the raw ore, that is, 0.550g collector is added per kilogram of raw ore), stir and adjust the slurry for 2 minutes, aerate and scrape the foam for 3 minutes, the foam is the roughing tailings; the roughing concentrate is obtained in the flotation cell;
[0073] Fine-grained process: The rougher concentrate is transferred to the flotation machine. The pH of the pulp is not adjusted. The compound collector is added. The dosage of fine-grained reagent is 350g / t (based on the weight of the raw ore, i.e., 0.350g collector is added per kilogram of raw ore). The pulp is stirred and adjusted for 1 minute, and then aerated and skimmed for 3 minutes. The foam is the fine-grained tailings. The product in the flotation cell is the quartz concentrate.
[0074] Results: The product obtained in the tank (quartz concentrate) had the following properties: SiO2 content 99.993%, Al2O3 content 0.0015%, and quartz concentrate recovery rate 93.2%.
[0075] Example 6
[0076] Raw materials: mineral processing feed from a quartz sand plant in Fengyang, Anhui Province (Al2O3 content 0.63%, SiO2 content 99.3%) after crushing and screening.
[0077] Reagent: Chlorinated N-hexadecylpyridine and phosphate-modified oleic acid are mixed in a mass ratio of 4:1.
[0078] process:
[0079] (1) Grind and screen the raw quartz ore to obtain 100% mineral powder with a particle size of 0.3mm to 0.1mm, and add water to adjust to obtain a slurry with a mass concentration of 16%;
[0080] (2) Add sulfuric acid to adjust the pH of the slurry to 3.4;
[0081] (3) Roughing operation: Add compound collector to the slurry, the amount of roughing agent is 500g / t (based on the weight of the raw ore, that is, 0.500g collector is added per kilogram of raw ore), stir and adjust the slurry for 2 minutes, aerate and scrape the foam for 3 minutes, the foam is the roughing tailings; the roughing concentrate is obtained in the flotation cell;
[0082] Fine-grained process: The rougher concentrate is transferred to the flotation machine. The pH of the pulp is not adjusted. The compound collector is added. The dosage of fine-grained reagent is 300g / t (based on the weight of the raw ore, i.e., 0.300g collector is added per kilogram of raw ore). The pulp is stirred and adjusted for 1 minute, and then aerated and skimmed for 3 minutes. The foam is the fine-grained tailings. The product in the flotation cell is the quartz concentrate.
[0083] Results: The product obtained in the tank (quartz concentrate) had the following properties: SiO2 content 99.991%, Al2O3 content 0.0017%, and quartz concentrate recovery rate 93.7%.
[0084] Comparative Example 1
[0085] The difference between this comparative example and Example 4 is that the reagent is entirely cationic N-hexadecylpyridine chloride, while the other steps are exactly the same as in Example 4.
[0086] Results: The product obtained in the tank (quartz concentrate) had a SiO2 content of 99.35%, an Al2O3 content of 0.61%, and a quartz concentrate recovery rate of 98.47%.
[0087] The results showed that in this comparative example, only N-hexadecylpyridine chloride was added, lacking the synergistic effect of phosphate-modified oleic acid. As a result, aluminosilicate gangue was difficult to effectively capture and enter the froth tailings, and most gangue impurities remained in the concentrate within the flotation cell; therefore, the removal of aluminum impurities was very poor. The high quartz concentrate recovery rate in this embodiment was due to the extremely low output of froth tailings during flotation, with the vast majority of ore solids remaining in the flotation cell, rather than the reagents achieving efficient separation.
[0088] The comparison between Example 4 and Comparative Example 1 demonstrates that N-hexadecylpyridine chloride alone has poor sorting effect; only when the two are combined can a synergistic effect be achieved, which can effectively remove aluminosilicate gangue while maintaining a high quartz recovery rate.
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 4 is that the reagent is a mixture of N-hexadecylpyridine chloride and phosphate-modified oleic acid in a mass ratio of 6:1, while the other steps are exactly the same as in Example 4.
[0091] Results: The product obtained in the tank (quartz concentrate) had a SiO2 content of 99.95%, an Al2O3 content of 0.03%, and a quartz recovery rate of 95.46%.
[0092] The results show that when the proportion of cations is too high, the selectivity of the compound system decreases and the removal effect of aluminum impurities deteriorates significantly, proving that the impurity removal performance deteriorates when the ratio exceeds the preferred range of this invention. The higher recovery rate of the quartz concentrate in this comparative example is due to insufficient removal of aluminosilicate gangue, leaving a large amount of impurities in the concentrate within the tank, rather than superior separation performance.
[0093] Comparative Example 3
[0094] The difference between this comparative example and Example 4 is that the reagent is a mixture of N-hexadecylpyridine chloride and phosphate-modified oleic acid in a mass ratio of 1:3, while the other steps are exactly the same as in Example 4.
[0095] Results: The product obtained in the tank (quartz concentrate) had the following composition: SiO2 content 99.94%, Al2O3 content 0.036%, and quartz recovery rate 88.12%.
[0096] The results showed that an excessively high proportion of anionic modified fatty acids led to an imbalance in the system's collecting capacity, a decrease in impurity removal efficiency, and a reduction in quartz recovery. This ratio was not conducive to flotation separation.
[0097] Comparative Example 4
[0098] The difference between this comparative example and Example 4 is that the collector is a mixture of industrial-grade dodecylamine (primary dodecylamine) and sodium petroleum sulfonate in a mass ratio of 3:1 (a commercially recognized effective reagent), and the specific flotation method is as follows:
[0099] (1) Grind and screen the raw quartz ore to obtain 100% mineral powder with a particle size of 0.3mm to 0.1mm, and add water to adjust it to obtain a slurry with a mass concentration of 18%;
[0100] (2) Add sulfuric acid to adjust the pH of the slurry to 3.2;
[0101] (3) Roughing operation: Add collector to slurry, the amount of roughing reagent is 400g / t (based on the weight of raw ore, that is, 0.400g collector is added per kilogram of raw ore), stir and adjust the slurry for 3min, aerate and scrape the foam for 8min, the foam is the roughing tailings; the roughing concentrate is obtained in the flotation cell;
[0102] Fine-grained process: The rougher concentrate is transferred to the flotation machine. The pH of the pulp is not adjusted. Collector is added continuously at a dosage of 300g / t (based on the weight of the raw ore, i.e., 0.300g collector per kilogram of raw ore). The pulp is stirred and conditioned for 3 minutes, then aerated and skimmed for 8 minutes. The foam is the fine-grained tailings. Collector is added again at a dosage of 200g / t (based on the weight of the raw ore, i.e., 0.200g collector per kilogram of raw ore). The pulp is stirred and conditioned for 2 minutes, then aerated and skimmed for 6 minutes. The foam is the fine-grained tailings. The product in the flotation cell is the quartz concentrate.
[0103] Results: The product obtained in the tank (quartz concentrate) had a SiO2 content of 99.5%, an Al2O3 content of 0.45%, and a quartz recovery rate of 80.5%. The effects of the ether amine collector and the collector of this invention are compared in Table 1 below.
[0104] Table 1. Performance comparison between the compound collector of this invention and commercially available etheramine collectors.
[0105]
[0106] The results show that commercially available dodecylamine can achieve a certain degree of aluminum impurity removal, but the loss of quartz particles during flotation is severe, and the recovery rate of quartz concentrate is significantly lower than that of the compound collector of this invention.
[0107] As can be seen from Comparative Examples 1-4, only when the ratio of chlorinated N-hexadecylpyridine and phosphate-modified oleic acid is controlled within a suitable range can both excellent aluminosilicate removal capacity and high quartz concentrate recovery rate be achieved. The overall performance of the compound system of this invention is superior to that of existing commercially available ether amine collectors.
[0108] The above description is a detailed description of the preferred embodiments of the present invention. However, the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modifications made under the technical spirit of the present invention should fall within the patent scope covered by the present invention.
Claims
1. A composite collector containing pyridine-based ionic liquids, characterized in that, The composite collector is mainly composed of a pyridine ionic liquid and phosphate-modified oleic acid in a mass ratio of 2 to 4:
1. The pyridine ionic liquid is N-chloroalkylpyridine, wherein the alkyl chain length is C12 to C18. The phosphate-modified oleic acid is prepared by epoxidation and ring-opening followed by phosphorylation.
2. The composite collector according to claim 1, characterized in that: The phosphate-modified oleic acid was prepared by the following method: S1 Epoxidation: Oleic acid and formic acid are mixed, heated to 55-65℃, and 30% hydrogen peroxide is added dropwise to carry out the epoxidation reaction. After the reaction is completed, the organic phase is separated and washed with water until neutral to obtain epoxy oleic acid; wherein, the mass ratio of oleic acid to formic acid is 100:8-12, and the mass ratio of oleic acid to hydrogen peroxide is 100:30-35. S2 acid-catalyzed ring-opening hydroxylation: Water and concentrated sulfuric acid catalyst are added to epoxy oleic acid, and the mixture is stirred vigorously at 70–80°C to carry out the ring-opening reaction to obtain hydroxy oleic acid; the mass ratio of epoxy oleic acid to water is 100:20–25, and the mass of concentrated sulfuric acid is 0.8%–1.2% of the mass of epoxy oleic acid; S3 Phosphoric acid esterification: Phosphorus pentoxide is added in batches to hydroxyoleic acid at 65-75℃ to carry out the esterification reaction. The molar ratio of hydroxyoleic acid to phosphorus pentoxide is 2.5-3:
1. After esterification, water is added for aging. S4 Neutralization: The system is cooled to below 40°C and neutralized with triethanolamine to a pH of 6.4–6.6 to obtain phosphate-modified oleic acid.
3. The composite collector according to claim 2, characterized in that: During the maturation process in step S3, the amount of water added is 4% to 6% of the total mass of the system, the maturation temperature is 65 to 75℃, and the maturation time is 1 to 2 hours.
4. The composite collector according to claim 1, characterized in that: The mass ratio of pyridine ionic liquid to phosphate-modified oleic acid in the composite collector is 3.3:
1.
5. The application of the composite collector according to any one of claims 1 to 4 in the flotation preparation of high-purity quartz.
6. The application according to claim 5, characterized in that, Includes the following steps: (1) The raw quartz ore is ground and pulped to obtain a slurry; (2) Add inorganic acid to adjust the pH of the slurry to 3.0-3.5; (3) Add the composite collector and perform at least one roughing flotation and one fine flotation.
7. The application according to claim 6, characterized in that: The total amount of the composite collector used is 800-900 g / t based on the mass of the raw ore.
8. The application according to claim 6, characterized in that: In step (3), the total time for adjusting the pulp and scraping bubbles in the roughing and fine flotation processes shall not exceed 5 minutes.
9. The application according to claim 6, characterized in that: In step (1), during pulping, the mass concentration of the pulp is controlled to be 15-20%.
10. The application according to claim 6, characterized in that: In step (1), the particle size distribution of the ore powder obtained by grinding is 0.1 mm to 0.3 mm.
Citation Information
Patent Citations
Method for separating feldspar and quartz under neutral condition
CN116689159A